Ecological aesthetics and ethics in the post epidemic era - Rolston, Holmes, 1932-2025, speaker; Bend, Ron, videographer (Colorado State University. Libraries, 2021)
The largest and most threatening pandemic in human history has humbled arrogant humans, locked us up. The virus in a couple months has stymied human achievements, aspirations, and freedoms. The upsetting surprise is that this tiny bit of nothing, not even alive, that you can't see even with a microscope, is upsetting our local and our global ecologies. We wonder why and how viruses can have their place in a wonderland biosphere. One big worry is that, developing a vaccine, we will miss this opportunity for more caring, love, and solidarity in our human communities, for pandemic justice. Biological nature is always giving birth, always in travail. Death is a necessary counterpart to the advancing of life. The music of life is in a minor key. The global Earth is a land of promise, and yet one that has to be died for. Earthen natural history might be called the evolution of suffering, or, equally, the evolution of caring. Life is perpetually perishing, yet perpetually regenerated, redeemed. In the post pandemic normal, it is impossible to go back to where we were. We must embrace nature and culture on Earth as it is and as it is becoming.
Dr. Rolston was invited to and prepared and delivered a video presentation to the International Symposium on the Development of Ecological Aesthetics in the Post Epidemic Era, held August 28-29, 2021 at Shangdong University, Shangdong, China.
Videographer: Ron Bend, CSU Media.
Includes Chinese text following Dr. Rolston's lecture.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: pandemic; virus; Covid 19; ecology; aesthetics; global Earth; wonderland; suffering; caring; new normal